1997
DOI: 10.1007/s004210050146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of muscle glycogen availability on maximal exercise performance

Abstract: This investigation determined the influence of pre-exercise muscle glycogen availability on performance during high intensity exercise. Nine trained male cyclists were studied during 75 s of all-out exercise on an air-braked cycle ergometer following muscle glycogen-lowering exercise and consumption of diets (energy content approximately 14 MJ) that were either high (HCHO(80% CHO) or low (LCHO-25% CHO) in carbohydrate content. The exercise-diet regimen was successful in producing differences in pre-exercise mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
9

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 28 publications
(49 reference statements)
6
34
0
9
Order By: Relevance
“…This may explain why carbohydrate intake and a high-carbohydrate diet do not affect time to exhaustion and anaerobic contribution during supramaximal exercise 6,27,28 . In this context, the study data reinforce the abovementioned results, showing that, like higher muscle glycogen content, an exogenous carbohydrate source has no positive effect on performance and anaerobic contribution during supramaximal exercise 5 . Although performance and anaerobic contribution did not change significantly, peak blood lactate had a moderate effect size (0.57), possibly because of higher pyruvate dehydrogenase complex activity, as reported by Galloway et al 3 .…”
Section: R E S U L T Ssupporting
confidence: 87%
See 1 more Smart Citation
“…This may explain why carbohydrate intake and a high-carbohydrate diet do not affect time to exhaustion and anaerobic contribution during supramaximal exercise 6,27,28 . In this context, the study data reinforce the abovementioned results, showing that, like higher muscle glycogen content, an exogenous carbohydrate source has no positive effect on performance and anaerobic contribution during supramaximal exercise 5 . Although performance and anaerobic contribution did not change significantly, peak blood lactate had a moderate effect size (0.57), possibly because of higher pyruvate dehydrogenase complex activity, as reported by Galloway et al 3 .…”
Section: R E S U L T Ssupporting
confidence: 87%
“…Bergström & Hultman 4 found that muscle glycogen is not completely depleted during high-intensity exercises, so it is not a limiting factor for exercise performance. Moreover, higher availability of muscle glycogen after a high-carbohydrate meal has no effect on performance during highintensity exercise 5,6 . A plausible explanation for better performance in high-intensity exercises after carbohydrate intake is higher neuromuscular activation, which may lead to higher recruitment of type IIx fibers 7 and concomitantly increase anaerobic glycolysis 8 .…”
Section: Introductionmentioning
confidence: 99%
“…39 , a 125% VO 2max , a supercompensação de glicogênio levou a um aumento de 56% na concentração muscular inicial desse composto, sem, no entanto, aumentar a tolerência ao esforço (~175 s), ou modificar o acúmulo de lactato e de pH sangüíneos. Resultados similares foram encontrados por Hargreaves et al 40 , que não identificaram nenhum efeito da supercompensação de glicogênio muscular sobre a potência de pico, potência média e máximo déficit acumulado de oxigênio em exercício de 75 segundos (75 all-out). Entretanto, em atividades com exigên-cia mista ou participação efetiva da capacidade lática (aeróbio-anaeróbio com duração entre 3 a 10 minutos, isto é, próximo ao VO 2max ), a depleção de glicogênio muscular pode interferir significativamente no desempenho.…”
Section: Efeito Da Intensidade Do Esforço No Metabolismo De Glicogêniunclassified
“…Logically, a reduction in training volume during taper with proper diet reverses this condition (Figure 2) [10,24]. Initial muscle glycogen levels do not seem to affect short-term high-intensity performance (i.e., a sprint) [31,32]. Indeed, the performance decrements from overtraining [33] and the performance benefits from taper [26] can occur independent of muscle glycogen levels during shorter duration activities.…”
Section: Taper and Muscle Energy Usagementioning
confidence: 98%